2014
DOI: 10.1016/j.ydbio.2014.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Junctionally restricted RhoA activity is necessary for apical constriction during phase 2 inner ear placode invagination

Abstract: After induction, the inner ear is transformed from a superficially located otic placode into an epithelial vesicle embedded in the mesenchyme of the head. Invagination of this epithelium is biphasic: phase 1 involves the expansion of the basal aspect of the otic cells, and phase 2, the constriction of their apices. Apical constriction is important not only for otic invagination, but also the invagination of many other epithelia; however, its molecular basis is still poorly understood. Here we show that phase 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…Other molecules that interact with this complex are also upregulated, such as rab25a , a Rab11 GTPase family member, as is celsr2, an atypical cadherin (Figure 7X–Y’). Celsr1, if reduced, causes otic defects because of loss of apical constrictions due to disturbed actomyosin recruitment to the apical junctional complex (Sai et al, 2014). RNASeq analysis also revealed the induction of cd9b by Notch, a Tetraspanin family member implicated in cell-matrix adhesion and Sdf1 (Cxcl12a) mediated migration (Figure 7L–M’, [Arnaud et al, 2015; Leung et al, 2011]).…”
Section: Resultsmentioning
confidence: 99%
“…Other molecules that interact with this complex are also upregulated, such as rab25a , a Rab11 GTPase family member, as is celsr2, an atypical cadherin (Figure 7X–Y’). Celsr1, if reduced, causes otic defects because of loss of apical constrictions due to disturbed actomyosin recruitment to the apical junctional complex (Sai et al, 2014). RNASeq analysis also revealed the induction of cd9b by Notch, a Tetraspanin family member implicated in cell-matrix adhesion and Sdf1 (Cxcl12a) mediated migration (Figure 7L–M’, [Arnaud et al, 2015; Leung et al, 2011]).…”
Section: Resultsmentioning
confidence: 99%
“…Junction shrinkage may occur by asymmetric, spatially restricted contraction of thin bundles positioned at different heights along the contacting neighbouring cells. This localized contraction enables apical constriction during invagination [73] or defines the topography of cell extrusion (apical or basal side of the epithelial monolayer). At the molecular level, cell extrusion directionality is driven by specific oncogenes (Ras, APC) [74,75] and the engagement of N-WASP or crosslinking proteins such as filamins or EPLIN [45,76,77].…”
Section: Thin Bundles and The Regulation Of Lateral Height And Junctimentioning
confidence: 99%
“…The morphogenetic changes that generate the otocyst from the otic placode have been investigated in the chick embryo [11]. Here, invagination to form the otic cup and otocyst involves two phases: an initial basal expansion of placodal cells, followed by their apical constriction.…”
Section: Early Ear Development: Otic Placode Induction and Otic Vesicmentioning
confidence: 99%
“…For example, a microarray study using an over-expression assay in Xenopus has identified nearly 30 genes expressed in the otocyst that are possible Six1 targets [10]. This and similar studies will provide not only a more complete picture of the transcriptional profile of early otic cells, but also new candidate genes for auditory disorders such as Branchio-Oto-Renal syndrome.The morphogenetic changes that generate the otocyst from the otic placode have been investigated in the chick embryo [11]. Here, invagination to form the otic cup and otocyst involves two phases: an initial basal expansion of placodal cells, followed by their apical constriction.…”
mentioning
confidence: 99%
See 1 more Smart Citation